Is coolness still cool?. Issue 4 (2nd October 2021) - Brown, Vanessa
ABSTRACT: In the 1990s and early 2000s, "cool' received substantial scholarly attention, some influential studies claiming that cool was becoming the dominant ethic in contemporary consumer societies, with increasingly global resonance. Yet it remains an elusive and complex phenomenon approached from numerous disciplinary islands, though sometimes curiously absent from studies of related phenomena such as fashion, 'authenticity', the 'hipster' and 'low affect'. In the light of developments since the early 2000s (including apparently substantial changes to the form and content of coolness), I argue here for the continued relevance of cool and the need for re-evaluation of key ideas of the 1990s and 2000s. The paper briefly suggests why cool has proved so tricky to work with, before identifying five key themes in existing studies, highlighting some contradictions which invite further endeavour, perhaps focused on renewed attention to cool in relation to forms of modernity.